2017
DOI: 10.1245/s10434-017-5953-9
|View full text |Cite
|
Sign up to set email alerts
|

A Single Institution Retrospective Comparison Study of Locoregional Recurrence After Accelerated Partial Breast Irradiation Using External Beam Fractionation Compared with Whole Breast Irradiation with 8 Years of Follow-Up

Abstract: IBTR rates were higher in external beam APBI group compared with WBI, but APBI had fewer toxicities. Clinicians must weigh the risks and benefits of APBI when making a recommendation for partial breast irradiation after lumpectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The good VMAT target coverage in the study was not at the expense of a high‐dose bath to healthy tissue. Reidunsdatter et al found that the V 40 Gy was a significant predictor of increased fatigue during RT 37 . However, the VMAT plans in the study were more conformal than the 3DCRT plans were; the latter was associated with a 17.8% larger tissue volume receiving a high dose (i.e., above 40 Gy) inside the external contour compared to the former.…”
Section: Discussionmentioning
confidence: 59%
“…The good VMAT target coverage in the study was not at the expense of a high‐dose bath to healthy tissue. Reidunsdatter et al found that the V 40 Gy was a significant predictor of increased fatigue during RT 37 . However, the VMAT plans in the study were more conformal than the 3DCRT plans were; the latter was associated with a 17.8% larger tissue volume receiving a high dose (i.e., above 40 Gy) inside the external contour compared to the former.…”
Section: Discussionmentioning
confidence: 59%
“…Shah et al reported on 290 patients treated with a more prolonged partial-breast irradiation regimen to 43.2 Gy in 16 fractions. 25 At a median follow-up of 8 years, there was no difference in ipsilateral breast recurrences between suitable, cautionary, and unsuitable patients, although recurrence after partial-breast irradiation did outpace whole-breast RT recurrences, highlighting the importance of appropriate patient selection. Jawad et al published a study on a larger cohort of 690 patients treated with a variety of APBI techniques (interstitial brachytherapy, balloon brachytherapy, and 3dimensional conformal external beam radiation).…”
Section: Discussionmentioning
confidence: 87%